IMPLEMENTATION OF IOT-BASED PRESENCE APPLICATIONS IN JUNIOR HIGH SCHOOLS TO SUPPORT IMPLEMENTATION SMART SCHOOLS - M Khairul Anam; zeki Kurniadi; Helda Yenni; Rometdo Muzawi; Khusaeri Andesa; Herwin Herwin (LPPM Nusa Mandiri, 2024)
This research is conducted to address the observed inefficiency in the current attendance process at SMP As-Syahira Amka in Pekanbaru. The traditional method of manually calling each student for attendance not only consumes time but also results in prolonged manual record-keeping processes. Recognizing the need for a more efficient and structured system, this study aims to introduce an IoT-based attendance solution using RFID technology. By implementing this solution, the research aims to enhance the efficiency of the attendance process, reduce administrative burdens, and improve overall school management. Additionally, the study aims to contribute to the advancement of educational technology by applying the Research and Development (R&D) method to design, develop, implement, and evaluate the proposed IoT-based attendance system. Ultimately, the goal of this research is to provide a practical and effective solution that can be adopted by SMP As-Syahira Amka and potentially other educational institutions facing similar challenges in attendance management. By introducing an IoT-based attendance system, it is hoped that there will be an improvement in efficiency, accuracy, and security in the attendance process, as well as a positive contribution to creating a more modern and structured learning environment. Moreover, this research may provide new insights into the utilization of technology in education in Indonesia and encourage the adoption of innovative solutions to enhance overall educational quality.